The Effects of PGPR Type and Application Intervals on The Growth and Yield of Cucumbers (Cucumis Sativus L.) - Septia Nur Aisyah; Pramono Hadi; Srie Juli Rachmawatie (Journal of Biodiversity and Biotechnology, 2026)
This study aimed to determine the effects of PGPR type and application interval on the growth and yield of cucumber plants. The study was conducted from October 26 to December 15, 2025, in Menjing Village, Jenawi Subdistrict, Karanganyar Regency, on Latosol soil at an elevation of 510 meters above sea level. This study employed a factorial design with a Randomized Complete Block Design (RCBD), consisting of two treatment factors and three replications. The first treatment factor was the type of PGPR (M), comprising three types (M1 = bamboo roots, M2 = mimosa pudica roots, and M3 = a mixture of bamboo and mimosa pudica roots). The second treatment factor, the PGPR application interval (P), consisted of three levels (I1 = 4 days, I2 = 8 days, and I3 = 12 days). The interaction between the type of PGPR treatment and the application interval had no significant effect on all observed parameters, with the best results observed in the combination of bamboo root PGPR treatment with a 4-day application interval (M1I1). The highest fruit weight of 11.61 kg/plot (60.48 tons/ha) was obtained in the M1I1 treatment combination (bamboo root PGPR applied at 4-day intervals). The lowest fruit weight of 8.19 kg/plot (42.64 tons/ha) was obtained in the M2I3 treatment combination (PGPR from mimosa roots applied at 12-day intervals).